La formazione degli insegnanti della secondaria in Italia e in Germania Una questione culturale - Ferrari, Monica (Collana di Pedagogia sociale, storia dell'educazione e letteratura per l'infanzia, 2021)
From an educational-historical point of view this book analyses the cultural models that underlie the conception and organisation of secondary teacher education and the professionalisation of future secondary school teachers in Europe. These models, based on different conceptions of school, citizenship and the teaching profession, have an enormous influence on school policy. Taking the examples of Italy and Germany, the complex history of teacher education is reconstructed and analysed. The articles deal, in a long-term perspective, with the emergence of national models of teacher education at the end of the 18th century, their consolidation in the 19th and 20th centuries and their transnational transformations between past and present.